Impact of exercise training on gut microbiome imbalance in obese individuals: a study based on Mendelian randomization analysis - Qian, Haonan; Zuo, Yuxin; Wen, Shixiong; Wang, Xilong; Liu, Yaowen; Li, Tianwei (Frontiers in Physiology, 2024)
ABSTRACT OBJECTIVE: The aim of this study was to investigate the relationship between exercise and gut Microbiome and to assess its possible causality. METHODS: Using Mendelian randomization (MR) research methods, we collected genetic data from different populations, including genetic variants associated with relative abundance or presence of microbial taxa as instrumental variables. At the same time, we extracted results related to obesity and gut Microbiome from existing relevant studies and used inverse variance weighting (IVW), weighted median, and MR-Egger regression to assess the causal relationship between obesity and gut Microbiome. We plotted forest plots and scatter plots of the association between obesity and gut Microbiome. RESULTS: gut Microbiome was positively associated with obesity, and four bacterial genera (Akkermansia, RuminococcaceaeUCG011, Holdemania, and Intestinimonas) were associated with obesity according to inverse variance-weighted estimation in at least one MR method. Inverse variance weighted estimation showed that obesity was associated with obesity in Akkermansia (OR = 0.810, 95% CI 0.608-1.079, P = 0.04), RuminococcaceaeUCG011 (OR = 1.238, 95% CI 0. 511-2.999, P = 0.04), Holdemania Intestinimonas (OR = 1.214 , 95% CI 1.002-1.470, P = 0.03), and Intestinimonas (OR = 0.747 , 95% CI 0.514-1.086, P = 0.01) had a relevant effect. Obesity decreased the abundance of Akkermansia, Intestinimonas microbiome and increased the abundance of RuminococcaceaeUCG011, Holdemania microbiome. CONCLUSION: The results of this study, conducted using a two-sample Mendelian randomization method, suggest a causal relationship between obesity and intestinal microbiome. Obesity decreased the abundance of Akkermansia, Intestinimonas microbiome and increased the abundance of RuminococcaceaeUCG011, Holdemania microbiome. More randomized controlled trials are necessary to elucidate the protective effects of exercise on gut Microbiome and its unique protective mechanisms.